PENGARUH BERCERITA DENGAN MEDIA REPLIKA TELEVISI BERGAMBAR TIGA DIMENSI TERHADAP KEMAMPUAN BERBICARA ANAK DI TAMAN KANAK-KANAK ISLAM DAUD KHALIFATULLOH PADANG - Wahyuni, Syartika Sri; Pransiska, Rismareni (Generasi Emas, 2019)
The purpose of this study is to know the influence of story telling by using the media of 3 dimension pictured replica television to children’s speaking ability at Padang Islam Daud Khalifatulloh Kindergarten. The method used  in this research is quantitative  in from of quasi experiment. The research shows that the children on experiment class of story telling using the media of 3 dimension pictured replica television to know their speaking ability have higher average score compared to control class which use pictured book as media in story telling to know children’s speaking ability. The average score of experiment class is 86,97 and average score of control class is 77,08. Based on data analysis tcount > ttable which is 4,28138 > 2,07387. It can be concluded that story telling activity using the media of 3 dimension pictured replica television has effect of children’s speaking ability at Padang Islam Daud Khalifatulloh Kindergarten years 2018/2019.